2015
DOI: 10.4997/jrcpe.2015.211
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and the risk of dementia – what do we know and what should we do?

Abstract: Summary'Being overweight can cut risk of dementia'. The news that a health status usually associated with poor outcomes and stigma may actually be protective for one of the most feared diseases of our time was enthusiastically greeted by the media and many individuals. The reports focused on this aspect -that risk of dementia fell with increasing body mass index (BMI) -although the authors of the study focused on the findings that being underweight in middle and old age carries an increased risk of dementia. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…A recent retrospective cohort study of almost two million individuals aged over 40 years in the UK, reported that being underweight in middle age and old age carries an increased risk of dementia ( 109 ) . This assertion is controversial and, in contrast to the evidence of an association between obesity and dementia, may reflect the tendency to underdiagnose dementia by general practitioners at the time the data were collected, and over or under adjustment for a number of factors such as competing risk of mortality as well as selection bias, and bias in the diagnosis of dementia in those with lower BMI/age ( 111 ) .…”
Section: The Obesity Paradoxmentioning
confidence: 99%
“…A recent retrospective cohort study of almost two million individuals aged over 40 years in the UK, reported that being underweight in middle age and old age carries an increased risk of dementia ( 109 ) . This assertion is controversial and, in contrast to the evidence of an association between obesity and dementia, may reflect the tendency to underdiagnose dementia by general practitioners at the time the data were collected, and over or under adjustment for a number of factors such as competing risk of mortality as well as selection bias, and bias in the diagnosis of dementia in those with lower BMI/age ( 111 ) .…”
Section: The Obesity Paradoxmentioning
confidence: 99%
“…Possible reasons for the association include increased glucose metabolism due to increased leg muscle mass. This may prevent the pathogenic effects of increased glucose availability due to glucose uptake into muscle [136][137][138][139].…”
Section: Absent Dementiamentioning
confidence: 99%